Developmental profiles of preschool children with delayed language development - Jeong Ji Eun; Hyung Jik Lee; Jin Kyung Kim (Korean Pediatric Society, 2014)
PurposeThis study examines changes in developmental profiles of children with language delay over time and the clinical significance of assessment conducted at age 2-3 years.MethodsWe retrospectively reviewed the medical records of 70 children (62 male, 8 female), who had visited the hospital because of delayed language development at 2-3 years, and were reassessed at ages 5-6. Language and cognitive abilities were assessed using multiple scales at the initial and follow-up visits.ResultsAt the initial test, 62 of the 70 children had mental development index (MDI) below 70 of Bayley Scales of Infant Development Test II. Of the 62 children in the follow-up assessment, 30 children (48.4%) remained within the same cognitive range (full-scale intelligence quotient, FSIQ<70 of Wechsler preschool and primary scale of intelligence), 12 had borderline intellectual functioning (FSIQ, 70-85), 6 improved to average intellectual functioning (FSIQ>85), and 5 had specific language impairment, 9 had autism spectrum disorders. At the initial test, 38 of the 70 children had cognitive developmental quotients (C-DQ) below 70. Of the 38 children in the follow-up assessment, 23 children (60.5%) remained within the same cognitive range (FSIQ<70). The correlation coefficient for MDI and FSIQ was 0.530 (P<0.0001) and that for C-DQ and FSIQ was 0.727 (P<0.0001). There was a strong correlation between C-DQ and FSIQ, and a moderate correlation between MDI and FSIQ.ConclusionLow MDI scores reflect a specific delay in cognitive abilities, communication skills, or both. The C-DQ, receptive language development quotient, and social maturity quotient also help to distinguish between children with isolated language delay and children with cooccurring cognitive impairment. Moreover, changes in the developmental profile during preschool years are not unusual in children with language delay. Follow-up reassessments prior to the start of school are required for a more accurate diagnosis and intervention.